PEMANFAATAN HASIL HUTAN BUKAN KAYU SEBAGAI BAHAN OBAT OLEH MASYARAKAT SEKITAR KAWASAN TAHURA NIPA-NIPA (STUDI KASUS KELURAHAN MANGGA DUA, KOTA KENDARI) - Niken , Pujirahayu; Laode Alimuddin; Harianti Harianti (Jurnal Ecogreen, 2016)
ABSTRACTThis study aimed to determine the types of Non Timber Forest Products which are used as  medicinal plants by the forest community around Tahura Nipa-Nipa Forest.  Research conducted around the Forest Estate Tahura Nipa-Nipa, Mangga Dua, District of Kendari, Southeast Sulawesi.   This research was conducted in February to Mey 2015. Mixed method of qualitative and quantitative approach was applied, while several collecting technique data were used in this study, namely interview, observation, vegetation survey, and literature study and analyzed by qualitative descriptive. The results of the identification of medicinal plant species is known that there are 22 species of plants that serve as medicine by the community.   Part of plants used to medicine are leaf, stem bark, fruit, seed,  root, or whole of plants.  How to processed medicinal plants used vary depending on the type of medicinal plants are crushed, bitten directly, squeezed, crushed, soaked and boiled singly or in mixtures that can treat certain diseases.Keywords : Tahura Nipa-Nipa, Medicinal Plants, Non-timber forests products.